MARRIAGE AND THE DEFECTS OF CONSENT UNDER CANON LAW - Vasco, Joceline Micaela Villa (ARACÊ, 2025)
The human being possesses an inner freedom that allows him/her to choose, which comes to consider consent as a true act. Therefore, it is understood that this freedom in marital consent corresponds to those who intend to contract marriage; otherwise, it would fall under the vices of consent set out in the Code of Canon Law (1983) from canon 1095-1103. Discretion of judgment or maturity in the decision to enter into the marital pact is one of the minimum requirements for its legitimacy. Therefore, in the absence of the conditions for marriage, the total nullity of the consensual pact will be incurred. This research employs a qualitative descriptive methodology, utilizing documentary and bibliographic techniques to gather and analyze relevant canonical texts and doctrinal sources. The development of the study is governed by a descriptive approach, based on documentary-bibliographic argumentation, which analyzes the Code of Canon Law in terms of the grounds for nullity due to defects of consent, in accordance with doctrinal and legal criteria referring to the historical context of marriage and the criteria for the evaluation of anomalies of consent. It is for this reason that the purpose and essential properties of marriage must be understood from the outset, given the importance of arguing by means of an exegetical criterion the causes of nullity in certain cases.